Aryl morpholino triazenes inhibit cytochrome P450 1A1 and 1B1. Issue 14 (15th July 2016) - Lee, Daniel; Perez, Pedro; Jackson, William; Chin, Taylor; Galbreath, Michael; Fronczek, Frank R.; Isovitsch, Ralph; Iimoto, Devin S.
Graphical abstract: Abstract: Many cytochrome P450 1A1 and 1B1 (CYP1A1 and CYP1B1) inhibitors, such as resveratrol, have planar, hydrophobic, aromatic rings in their structure and exhibit anti-cancer activity. Aryl morpholino triazenes have similar structural features and in addition contain a triazene unit consisting of three consecutive, conjugated nitrogen atoms. Several aryl morpholino triazenes, including 4-[( E )-2-(3, 4, 5-trimethoxyphenyl)diazenyl]-morpholine (2 ), were prepared from a reaction involving morpholine and a diazonium ion produced from different aniline derivatives, such as 3, 4, 5-trimethoxyaniline. The aryl morpholino triazenes were then screened at 100 μM for their ability to inhibit CYP1A1 and CYP1B1 using ethoxyresorufin as the substrate. Triazenes that inhibited the enzymes to less than 80% of the uninhibited enzyme activity were assayed to determine their IC50 value. Compound2 was the only triazene to inhibit both CYP1A1 and CYP1B1 to the same degree as resveratrol with IC50 values of 10 μM and 18 μM, respectively. Compounds3 and6 selectively inhibited CYP1B1 over CYP1A1 with IC values of 2 μM and 7 μM, respectively. Thus, aryl morpholino triazenes are a new class of compounds that can inhibit CYP1A1 and CYP1B1 and potentially prevent cancer.